To test or not to test? Laboratory support for the diagnosis of Lyme borreliosis: a position paper of ESGBOR, the ESCMID study group for Lyme borreliosis. (February 2018) - Dessau, R.B.; van Dam, A.P.; Fingerle, V.; Gray, J.; Hovius, J.W.; Hunfeld, K.-P.; Jaulhac, B.; Kahl, O.; Kristoferitsch, W.; Lindgren, P.-E.; Markowicz, M.; Mavin, S.; et al.
Abstract: Background: Lyme borreliosis (LB) is a tick-borne infection caused by Borrelia burgdorferi sensu lato . The most frequent clinical manifestations are erythema migrans and Lyme neuroborreliosis. Currently, a large volume of diagnostic testing for LB is reported, whereas the incidence of clinically relevant disease manifestations is low. This indicates overuse of diagnostic testing for LB with implications for patient care and cost-effective health management. Aim: The recommendations provided in this review are intended to support both the clinical diagnosis and initiatives for a more rational use of laboratory testing in patients with clinically suspected LB. Sources: This is a narrative review combining various aspects of the clinical and laboratory diagnosis with an educational purpose. The literature search was based on existing systematic reviews, national and international guidelines and supplemented with specific citations. Implications: The main recommendations according to current European case definitions for LB are as follows. Typical erythema migrans should be diagnosed clinically and does not require laboratory testing. The diagnosis of Lyme neuroborreliosis requires laboratory investigation of the spinal fluid including intrathecal antibody production, and the remaining disease manifestations require testing for serum antibodies to B. burgdorferi . Testing individuals with non-specific subjective symptoms is not recommended, because of a low positive predictive value. Graphical abstract: